MicroRNAs link chronic inflammation in childhood to growth impairment and insulin-resistance. (February 2018) - Cirillo, Francesca; Lazzeroni, Pietro; Catellani, Cecilia; Sartori, Chiara; Amarri, Sergio; Street, Maria Elisabeth
Graphical abstract: Highlights: Poor linear growth with subsequent reduction in adult height is a frequent complication in childhood chronic inflammatory diseases. Children with inflammatory conditions are at risk of developing insulin-resistance as a result of the inflammatory process. MicroRNAs in inflammatory conditions show changes and represent an interesting link between growth impairment and insulin-resistance. MicroRNAs represent a promising diagnostic tool and a new direction for treatment strategies also in the field of immunometabolism. Abstract: MicroRNAs are involved in multiple pathophysiological networks and in the pathogenesis of a broad spectrum of human disorders, including cancer and inflammatory diseases. Impaired linear growth is encountered in children with chronic inflammatory conditions such as cystic fibrosis, inflammatory bowel diseases, juvenile idiopathic arthritis, celiac disease and in subjects born intrauterine growth restricted/small for gestational age. Children with inflammatory conditions may also be at risk of developing insulin resistance as a result of the inflammatory process and concurrent therapy. Chronic inflammation may lead to a continuum of abnormalities in the Growth hormone/Insulin-like growth factor 1 (GH/IGF-I) axis, including relative GH insufficiency, GH/IGF-I resistance due to down regulation of GH and IGF-I receptors, changes in GH and IGF-I bioavailability due to modifications of binding proteins, and/or impaired GH/IGF-I signaling. The aim of this review is first to summarize the current knowledge concerning microRNAs involved in inflammation in the most relevant chronic inflammatory diseases in childhood, second to provide new insights into miRNA regulation of growth and insulin sensitivity mediated by the inflammatory processes. We evaluated single microRNAs involved in inflammation in the single conditions mentioned above and verified which had validated and predicted targets within the GH receptor, IGF-I type 1 receptor and insulin receptor interactomes. The findings show a new link among inflammation, growth and insulin sensitivity mediated by miRNAs that warrants further research in the future.